Intencjonalność badacza kultury w poszukiwaniu prawdy (dominujący fantazmat) - Doda-Wyszyńska, Agnieszka (Humaniora. Czasopismo Internetowe, 2019)
The contemporary experience of rationality is the relationship of a multi-faceted break with the value of truth. Today we are observing the paradoxical return of the final questions, which could not be denied and pushed beyond culture. Admittedly, it was attempted to change the culture into the domain of organizing temporal life, but it failed. Although, predicting victory in any game (in the Bourdieu sense) has become impossible, the desire to experience meaning is repeatedly coded in us by humanists. After losing culture, we live in a constant trauma that we can not overcome. Today there is no reference to the truth produced within symbolic capital. In addition, we are in the phantasm of universal consent.